The effectiveness of PRO-STEM module on students’ higher order thinking skills (HOTS) - Nurul Huda Kasim,; Che Nidzam Che Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The development of higher order thinking skills (HOTS) requires a teaching approach that encourages students’ inquiry skills as being emphasized in science, technology, engineering, and mathematics (STEM) education. This study aims to develop and examine the effectiveness of the PRO-STEM Module on students’ HOTS. The module employed project-based learning (PjBL) approach with the integration of the STEM concept in Biodiversity and Ecosystem topics. This study involved quasi-experimental design to study the effectiveness of the module. A total of 63 secondary school students were involved in this study. They were divided into control group (30 students) and treatment group (33 students). The findings showed that the intervention using PRO-STEM module has significantly increased their HOTS mean score (t(61)=- 2.61, p=.01). This implicates that PjBL with the integration of the STEM concept in the PRO-STEM Module is an innovation in the teaching and learning of science that further enhances students' HOTS and understanding in Biodiversity and Ecosystem topics.